PENERAPAN MODEL PEMBELAJARAN TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS I SDN 010 BANJAR PANJANG KECAMATAN KERUMUTAN - Sri Nurdiyati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low result of learning math class I SDN 010 BanjarPanjang Kecamatana Kerumutan. Of the 30 students only 12 students (40.00%), for the studydoing research by applying the learning model guided by the goal of improving learningoutcomes in mathematics. This research is a class act who performed two cycles. The dataused in this study focused on improving learning outcomes and increase student masterylearning. The study states that the application of guided learning model can improve students'mathematics learning outcomes, as evidenced by: the preliminary data the number of studentswho pass are 12 students (40.00%) increased in the first cycle by the number of students whocompleted is 20 students (66 , 67%) and increased in the second cycle by the number ofstudents who completed is 27 students (90.00%).